The Association Between Quantitative Flow Ratio and Intravascular Imaging-defined Vulnerable Plaque Characteristics in Patients With Stable Angina and Non-ST-segment Elevation Acute Coronary Syndrome - Zuo, Wenjie; Sun, Renhua; Zhang, Xiaoguo; Qu, Yangyang; Ji, Zhenjun; Su, Yamin; Zhang, Rui; Ma, Genshan (Frontiers in Cardiovascular Medicine, 2021)
Background: This study aimed to examine whether quantitative flow ratio (QFR), an angiography-based computation of fractional flow reserve, was associated with intravascular imaging-defined vulnerable plaque features such as thin cap fibroatheroma (TCFA) in patients with stable angina and non-ST-segment elevation acute coronary syndrome. Methods: Patients undergoing optical coherence tomography (OCT) or intravascular ultrasound (IVUS) examinations were identified from 2 prospective studies and their interrogated vessels were assessed with QFR. Lesions in the OCT cohort were classified into tertiles: QFR-T1 (QFR ≤0.85), QFR-T2 (0.85< QFR ≤0.93), and QFR-T3 (QFR >0.93). Lesions in the IVUS cohort were classified dichotomously as low or high QFR groups. Results: This post-hoc analysis included 132 lesions (83 for OCT and 49 for IVUS) from 126 patients. The prevalence of OCT-TCFA was significantly higher in QFR-T1 (50%) than in QFR-T2 (14%) and QFR-T3 (19%) (p = 0.003 and 0.018, respectively). Overall significant differences were also observed among tertiles in maximum lipid arc, thinnest fibrous cap thickness, and minimal lumen area (p = 0.017, 0.040, and <0.001, respectively). Thrombus was more prevalent in QFR-T1 (39%) than in QFR-T2 (3%) and QFR-T3 (12%) (p = 0.001 and 0.020, respectively). In the multivariable analysis, QFR≤0.80 remained as a significant determinant of OCT-TCFA regardless of the presence of NSTE-ACS and the level of low-density lipoprotein cholesterol (adjusted OR: 4.387, 95% CI 1.297 to 14.839, p = 0.017). The diagnostic accuracy of QFR was moderate in identifying lesions with OCT-TCFA (area under the curve: 0.72, 95% CI 0.58–0.86, p = 0.003). In the IVUS cohort, significant differences were found between 2 groups in minimal lumen area and plaque burden but not in the distribution of virtual histology (VH)-TCFA (p = 0.025, 0.036, and 1.000, respectively). Conclusions: Lower QFR was related to OCT-defined plaque vulnerability in angiographically mild-to-intermediate lesions. The QFR might be a useful tool for ruling out high-risk plaques without using any pressure wire or vasodilator.